DIVERGÊNCIAS E CONVERGÊNCIAS ENTRE A COMUNICAÇÃO PRIMÁRIA E A COMUNICAÇÃO SECUNDÁRIA NA DIVULGAÇÃO DO CÂNCER DE MAMA - Bertol, Sônia Regina Schena (2007)
The present study investigates the convergences and divergences in the primary and secondary communication pertaining breast cancer. We used an interpretation method provided by Framing Theory, Agenda Setting, Social Learning Theory, Diffusion of Innovations, Semiotics and the concept of the News (like information about recent events), basing our argument on the fact that scientists and journalists communicate scientific news under a different light. Another objective of our study was to draw a historical view on the Health Communication and its evolution, taking into consideration that the communication field has undertaken an enormous effort to stablish a relationship with the health field, creating an area to apply theories, principles and communication techniques, with the clear objective of dissemination and sharing of information, knowledge and practices that can contribute to improve the health and wellness of the population. We found considerable supporting material through the analysis of data from scientific and journalistic periodicals which publish news regarding breast cancer. The implications of such differences between primary communication (among peers) and secondary communication (general public) for the health communication are sometimes presented as convergences, and sometimes as divergences. When they are presented in a clear and understandable manner, they represent an advancement to Health Communication, bringing positive results for the well being of the population, taking into consideration that the origin of the diseases lies, fundamentally, where the biological and social dimensions intertwine.(AU)